PENGELUARAN R&D DAN KINERJA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA YANG DIMODERASI OLEH USIA PERUSAHAAN - Setiawan, Rahmat; Harmasanto, Denny Hardiko (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2019)
The purpose of this study is to examine the effect of research and development expenditure on the company's financial performance and prove the influence of corporate age moderation. The research population consisting of 140 manufacturing companies listed on the Indonesia Stock Exchange was selected using the purposive sampling method. The final sample size is 113 companies that provide annual financial statements from 2012-2017. The unbalanced panel data analysis uses variables in the company's annual reports that are tested using OLS regression. The results found that companies investing in R&D experienced a 3% increase in sales compared to companies that did not spend in R&D. Further testing also found that the age of the company moderated the relationship between R&D expenditure and financial performance, where older companies that invest in R&D produced 0.1% more sales and 0.6% higher profits than younger companies in the manufacturing industry. The conclusion of this study is that the effect of R&D expenditure on sales and net profit cannot be directly felt in the current year. R&D spending like other types of investment requires time to be able to contribute to the company's sales and net profit. The findings of this study provide support that R&D spending is a driving force for innovation in endogenous growth theories